Development of a Gamification-Based Problem-Based Learning Model to Enhance Speed Reading Skills of Fifth-Grade Elementary School Students - Adlani, Salsabillah; Andajani, Kusubakti; Anggraeni, Ade Eka (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Many students struggle with reading, and their skills have declined significantly due to learning loss observed in schools. Students find it difficult to comprehend text, lose focus, and show decreased motivation. Meanwhile, reading skills are crucial for students as they serve as the foundation of 21st-century competencies and support learning across all subjects. This condition demands learning innovations that not only train reading speed but also enhance motivation through interactive approaches. The objectives of study are : (1) to develop a Problem-Based Learning (PBL) model integrated with gamification for improving the speed reading skills of fifth-grade elementary students in the from of a teacher’s guidebook that is feasible for used, and (2) to test the validity of the model. The research employed a Research and Development (RD) method using the ADDIE model and was conducted at SDN 1 Gading Kembar, SDN 3 Asrikaton, and SDN 3 Saptorenggo. Research instruments included expert validation, implementation observation, students' response questionnaires, and speed reading tests. The results showed that expert validation reached 87.25% (very valid), model implementation achieved 93% (vary practical), and effectiveness was indicated by an increase in reading speed from 121 words per minute (wpm) to 185 wpm with an N-Gain of 0.52 (moderated).The study concludes that the gamified PBL model is effective in improving both students’ speed reading skills and their motivation. This is supported by gamification elements (points, levels, challenges, leaderboards) and the PBL syntax, which foster collaboration, problem-solving, and active learning engagement.